Review on Natural Fibers Based Nanocomposite Materials: Part - I - KADAM, DATTATREYA M.; KAUR, AMANPREET (Cotton Research Journal, 2021)
Biocomposites have vast applications in today’s era due to its light in weight, biodegradability and high strength etc in many fields. A composite material is produced from two (or more) distinct constituent materials with different physical and chemical properties which together result in a material with entirely different properties. These are classified into four types as particulate, fibre, laminate and hybrid composites on the basis of the reinforcement material used. Biocomposites are materials produced by a matrix (resin) and a reinforcement of natural fibers. Natural fibres are divided into three types based on their origin into animal, vegetable and mineral fibres and showed numerous advantageous characteristics in comparison to the synthetic fibres which include low cost, high strength to weight ratio, acceptable strength and have renewable and degradation properties, non- corrosive property, low density per unit volume and cause less health and environmental hazards. Main constituents of any lignocellulosic source are cellulose, hemicellulose and lignin and their quantity varies from one plant to another. Three hydrolysis processes are involved in the production of sugars and their conversion to ethanol and these are dilute acid, concentrated acid, and enzymatic hydrolysis. Different parameters were taken into account for the characterization studies of the cellulose crystals derived from the different sources and these are crystallinity index, surface morphology, topography, structural, elemental, thermal stability and their reinforcing capability.